The Incidence, Predisposing Factors, Complications and Outcome of Preeclampsia in Diabetic Pregnancy - Jesmin, S; Jahan, S; Khan, MI; Sultana, N; Jerin, J; Habib, SH; Paul, D (BIRDEM Medical Journal, 2012)
Introduction: Preeclampsia is a serious complication of pregnancy and common cause of fetal and maternal morbidity as well as mortality worldwide. In diabetic women, the chance of preeclampsia is increased. The incidence of preeclampsia in diabetic pregnancy is approximately 10 to 15 percent, which is associated with poor glycaemic control. Aim: This study was carried out to find the predisposing factors related to preeclampsia and determine the complications of preeclampsia in diabetic pregnancy and also the impact of preeclampsia in infants born to diabetic mothers. Methods: This prospective study was carried out at the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. The Patient population consisted of 80 diabetic pregnant women who attended or admitted to BIRDEM hospital during the study period. The women were divided into groups: 50 pregnant diabetic women with preeclampsia were taken as case. 30 pregnant diabetic women without preeclampsia were taken as control. Diagnosis of preeclampsia was made on the basis of the criteria of the Committee on Terminology of the American College of Obstetrician and Gynecologist. Results: Preterm delivery (<37 weeks gestation) was higher among study group (64%) compared to control (33.3%) women. Term delivery was 36.0 vs 66.7 percent among case and control women, respectively. The distribution is statistically significant (P<0.01). 35 percent of Caesarean section was done due to fetal distress in the study group and in control group it was 20 percent. In study group, 22.5 percent Caesarean sections were done due to impending eclampsia and eclampsia, 705 percent due to accidental haemorrhage and 5 percent due to IUGR. Maternal complication in study and control subjects. In the case group, maximum number of the women (16%) showed signs of impending eclampsia, while among control women, maximum number (10%) developed postpartum haemorrhage (PPH). 48 percent neonates were of low birth weight and in controls it was 13.3 percent. Both hyperbilirubinaemia (40%) and hypoglycaemia (30%) were more in study group than controls (16.66% and 20%, respectively). Perinatal outcome among study group and controls. Neonatal survival was 82.0 percent in study group and 86.7 percent in control group. Comparison of Perinatal outcome between the groups is not statistically significant. Most of the perinatal mortality was due to prematurity (8%) and intrauterine death (6%). In control group, most of the perinatal deaths were due to congenital anomalies (6.6%). Conclusion: The higher incidence among study group may be, in part, the result of more preterm birth or shortened gestational duration because early delivery is a consequence of preeclampsia. The higher rate in associated with preeclampsia was due to increased incidence of IUD and prematurity. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12379 Birdem Med J 2011; 1(1): 10-14